The Effects of Climate-Related Factors on the Incidences of Malaria Cases in the Braced States, Nigeria - Alexander, E.O. (Department of Geography, University of Colombo, 2025)
Nigeria accounts for around 25% of all malaria cases worldwide, making it a severe nationwide public concern. The study examines the effects of temperature, vapour pressure, diurnal temperature range (DTR), and rainfall on the number of instances of malaria in the BRACED States, Nigeria. The climatic data employed in this research were generated from Climate Research Unit (CRU) TS v 4.07 with high-resolution grids of 5o x 5o latitudes and longitudes time series data from January 1962 – December 2021, while the number of malaria cases was generated from the Ministry of Health offices. The climatic data and the number of malaria cases obtained were analysed with descriptive and inferential statistical techniques. The results of fixed effect (FE) and random effects (RE) regression showed that malaria had a weak positive relationship with temperature (0.3614) and Vapour pressure (0.3015), while a weak negative relationship was found between malaria and rainfall (-0.4155) and DTR (- 0.1697). Therefore, for effective malaria control and elimination strategies, the study recommends that insecticide-treated bed nets (ITNs) should be distributed in large quantities to homes, giving priority to high-transmission areas and to those who are most susceptible, such as pregnant women and children.
Keywords: Climate-Related Factors; Diurnal Temperature Range (DTR; Malaria; Rainfall; NATURAL SCIENCES::Physics::Condensed matter physics::Low temperature physics; Vapour Pressure